Empiric antibiotic, mechanical ventilation, and central venous catheter duration as potential factors mediating the effect of a checklist prompting intervention on mortality: an exploratory analysis - Weiss Curtis H; Persell Stephen D; Wunderink Richard G; Baker David W (BMC, 2012)
Abstract Background Checklists are clinical decision support tools that improve process of care and patient outcomes. We previously demonstrated that prompting critical care physicians to address issues on a daily rounding checklist that were being overlooked reduced utilization of empiric antibiotics and mechanical ventilation, and reduced risk-adjusted mortality and length of stay. We sought to examine the degree to which these process of care improvements explained the observed difference in hospital mortality between the group that received prompting and an unprompted control group. Methods In the medical intensive care unit (MICU) of a tertiary care hospital, we conducted face-to-face prompting of critical care physicians if processes of care on a checklist were being overlooked. A control MICU team used the checklist without prompting. We performed exploratory analyses of the mediating effect of empiric antibiotic, mechanical ventilation, and central venous catheter (CVC)duration on risk-adjusted mortality. Results One hundred forty prompted group and 125 control group patients were included. One hundred eighty-three patients were exposed to at least one day of empiric antibiotics during MICU admission. Hospital mortality increased as empiric antibiotic duration increased (P<0.001). Prompting was associated with shorter empiric antibiotic duration and lower risk-adjusted mortality in patients receiving empiric antibiotics (OR 0.41, 95% CI 0.18-0.92, P=0.032). When empiric antibiotic duration was added to mortality models, the adjusted OR for the intervention was attenuated from 0.41 to 0.50, suggesting that shorter duration of empiric antibiotics explained 15.2% of the overall benefit of prompting. Evaluation of mechanical ventilation was limited by study size. Accounting for CVC duration changed the intervention effect slightly. Conclusions In this analysis, some improvement in mortality associated with prompting was explained by shorter empiric antibiotic duration. However, most of the mortality benefit of prompting was unexplained.